Land-use systems regulate carbon geochemistry in the temperate Himalayas, India. (15th October 2022) - Kumar, Shamal Shasang; Mir, Shakeel Ahmad; Wani, Owais Ali; Babu, Subhash; Yeasin, Md; Bhat, M.A.; Hussain, Nazir; Ali Wani, Anas Ibni; Kumar, Rajesh; Yadav, Devideen; Dar, S.R.
Abstract: The Himalayan ecosystem is critical for ecological security and environmental sustainability. However, continuous deforestation is posing a serious threat to Himalayan sustainability. Changing land-use systems exert a tenacious impact on soil carbon (C) dynamics and regulate C emissions from Himalayan ecosystem. Therefore, this study was conducted to determine the changes in different C pools and associated soil properties under diverse land-use systems, viz. natural forest, natural grassland, maize field converted from the forest, plantation, and paddy field of temperate Himalaya in the surface (0–20 cm) and subsurface (20–40 cm) soils. The highest total organic carbon (24.24 g kg −1 ) and Walkley-black carbon contents (18.23 g kg −1 ), total organic carbon (45.88 Mg ha −1 ), and Walkley-black carbon stocks (34.50 Mg ha −1 ) were recorded in natural forest in surface soil (0–20 cm depth), while soil under paddy field had least total organic carbon (36.45 Mg ha −1 ) and Walkley-black carbon stocks (27.40 Mg ha −1 ) in surface soil (0–20 cm depth). The conversion of natural forest into paddy land results in 47.36% C losses. Among the cultivated land-use system, minimum C losses (29.0%) from different pools over natural forest system were reported under maize-filed converted from forest system. Land conversion causes more C losses (21.0%) in surface soil (0–20 cm depth) as compared to subsurface soil. Furthermore, conversion of forest land into paddy fields increased soil pH by 5.9% and reduced total nitrogen contents and microbial population by 28.0% and 7.0%, respectively. However, the intensity of total nitrogen and microbial population reduction was the lowest under maize fields converted from the forest system. The study suggested that the conversion of natural forest to agricultural land must be discouraged in the temperate Himalayan region. However, to feed the growing population, converted forest land can be brought under conservation effective maize-based systems to reduce C loss from the intensive land use and contribute to soil quality improvements and climate change mitigation. Graphical abstract: Image 1 Highlights: Five Land uses were assessed for TOC and WBC dynamics. Natural forests had the highest TOC and WBC stocks in soil profile (0–40 cm). Conversation of forest land to crop land accelerates the soil C losses. The lowest soil C losses was observed in conservation effective maize based system.